IDENTIFIKASI FAKTOR PENDORONG ANAK PEREMPUAN BERAKTIVITAS DI JALANAN (Suatu Studi Terhadap Anak Jalanan Perempuan di Kota Pekanbaru) - Basri Basri; Yoserizal Yoserizal (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2019)
In Pekanbaru City, more and more female street children are found. They used to roam the crossroads, at the "red light" intersection, on pedestrian bridges, in the shops, and in shopping centers. To anticipate the existence of female street children in Pekanbaru City, the Pekanbaru Social Service as an agency that has authority in handling female street children, has recruited these female street children and returned them to their home areas and to their parents' homes. However, the existence of female street children in the city of Pekanbaru remains a daily sight and in fact, some of them are old faces that have been repatriated. The research objective was first, to identify the social and cultural characteristics of female street children in Pekanbaru City. Second, comprehensively analyze the factors that cause girls to move on the streets. The research method is quantitative descriptive. The population in this study were all female street children in Pekanbaru. From this population, a list of all female street children will be created. From the number, the sample will be taken by simple random sampling. The results of the study showed that out of 115 street children the respondents were aged 4 to 18 years and the most aged between 12 and 14 years (45.22%). Seeing the age of street children who have school age, it turns out that 69.57 percent are not in school. While those who were still in school the education level (74.26%) had elementary school education and (25.74%) were in junior high school. The dominant reason done by street children originating from within themselves is on their own desires and that desire arises because of the economic conditions of the family. It seems that the reasons they put forward on their own are (59.13%) with the aim of helping parents (37.39 %) helps school fees 23.48 percent to find food (21.74%).